Pelatihan Tata Kelola Keuangan Bagi Pelaku UMKM pada Objek Wisata Situ Tandon Ciater, Kota Tangerang Selatan - Rahman, Fakung; Sulaiman Anhary, Agus; Dwianggoro, Prihadi (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2023)
This Community Service (PkM) is entitled Training in Making Simple Cash Flow Reports for MSMEs in Tandon Ciater, Kel. Buaran, District. Serpong, South Tangerang City. The method used is a survey method and direct delivery of material, guidance and assistance in the practice of making a simple cash flow report specifically for MSMEs who conduct their business in Tandon Ciater. The conclusion of this PkM program is that it has not yet achieved maximum results, but efforts to continue this service will be sustainable until the MSMEs in Tandon Ciater are at least able and understand how to make their own simple cash flow reports. If the MSME players are able and skilled at making simple cash flow reports, the PkM plan for the next semester will be implemented at this place as well and will provide training on how to calculate cost of goods production, cost of goods sold and calculate profit and loss reports.